First record of gregarine protists (Apicomplexa: Sporozoa) in Asian fungus-growing termite Macrotermes barneyi (Blattaria: Termitidae) - Zhang, Shuo (Sci Rep, 2021)
Macrotermes barneyi, widely distributed in southern China, is the major fungus-growing termite in the subfamily Macrotermitinae. It has no flagellated protists in the guts. Here, we report occurrence of gregarine, a protozoan parasite in the digestive tract of M. barneyi. The general morphology and ultrastructure of the gregarine gamonts and syzygies by light micrograph and scanning electron micrograph are presented. SSU rDNA sequence analysis showed that the termite gregarine has the highest identity (90.10%) to that of Gregarina blattarum from cockroaches. Phylogenetic analysis based on the SSU rDNA sequences from diverse insect eugregarines indicated that the gregarine from M. barneyi is phylogenetically close to G. blattarus, L. erratica and G. tropica from Gregarinidae and Leidyanidae families, and may represent a novel species. This study expands our knowledge about the diversity of terrestrial eugregarines parasitizing in termites.